PENERAPAN KONSEP REPRESENTASI PADA MUSIC VIDEO TINKERBELLE BALI DI DEWATLANTIS STUDIO - Ida bagus Putu Bayu Krisnanda; I Wayan Suardana; Gede Pasek Putra Adnyana Yasa (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Tinkerbelle Bali's music video has a goal to become an audio-visual work that has very strong value and has an impact on the wider community. It is hoped that the stigma of metal bands that is still bad can provide space for the Tinkerbelle band to be able to speak and communicate through music videos that apply the concept of representation in order to interpret the harmony of music and lyrics into visual images that can be enjoyed by people from all walks of life. The music video created by the author is able to become an important part for Tinkerbelle Bali in pursuing existence in the world of the music industry. This work is based on research and observations on the genre chosen by the Tinkerbelle Band in order to understand and understand the meaning of every melody and lyrics that are created. The method used is representation in the application of semiotics which is supported by the concept of mise en scene so as to create a new interpretation of how metal music communicates through songs. This trilogy music video work applies signs and symbols as semiotics which are poured into various elements of mise en scene. The concept of directing representation is very commonly created but its application uses hard, abstract elements in the metal music genre to be watched by the general public without exception for people who do not have an interest in metal music so that the writer is able to present a very unique and entertaining show for the audience. Public.